The Acute Effect of Imagery and Touchpad Training on Improving The Performance of Paragliding Athletes - Dian Listiarini; Rian Kurniawan; Syamsul Ma'arif (Jurnal Ilmu Keolahragaan Undiksha, 2024)
Lack of a combination of physical and mental training results in paragliding athletes lacking focus and confidence and not getting good accuracy results. The main aim of this research is to find out about exercise parable And touchpad towards increasing the performance of paragliding athletes in accuracy numbers in Central Java. The method used is quantitative one group pre-test post-test design. The population was 14 regional paragliding athletes and the sampling technique used total sampling 14 paragliding athletes. The pre-test and post-test carry out flying accuracy 3 times with points calculated as accumulated. The research instrument is skytronik 22-centimeter diameter. The main results of the study were significant differences in points before and after exercise. The conclusion is that imagery and touchpad training can improve the performance of paragliding athletes in accuracy numbers in Central Java. The implications of this research are implications This research shows that these two methods have significant implications in improving athlete performance.